The synergy between Expanded Program on Immunization and Polio Eradication Initiative in Pakistan: a policy and program exploration - Zaeem Haq; Arshad K. Chandio; Shamsa Zafar; Faisal Iqbal; Ayesha Naeem; Saad Karim (Journal of Global Health Reports)
# Background Until recently, Pakistan had achieved significant milestones in polio eradication, and was close to becoming polio-free. The country has an Expanded Program on Immunization (EPI) since 1978 and a Polio Eradication Initiative (PEI) since 1994. PEI and EPI need to carry out synergized activities during the last leg of polio eradication; EPI taking over the responsibility for a polio-free Pakistan. Knowing the understanding and implementation of the synergy between the two programs is important at this critical juncture.